2017
DOI: 10.1186/s12967-017-1296-3
|View full text |Cite
|
Sign up to set email alerts
|

Report on the first SLFN11 monothematic workshop: from function to role as a biomarker in cancer

Abstract: SLFN11 is a recently discovered protein with a putative DNA/RNA helicase function. First identified in association with the maturation of thymocytes, SLFN11 was later causally associated, by two independent groups, with the resistance to DNA damaging agents such as topoisomerase I and II inhibitors, platinum compounds, and other alkylators, making it an attractive molecule for biomarker development. Later, SLFN11 was linked to antiviral response in human cells and interferon production, establishing a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
6
20
0
Order By: Relevance
“…Among those drugs for which gene expression data can reasonably predict a cancer cell line's sensitivity, we identified many known drug-gene interactions as well as several novel associations. Our results are consistent with and lend additional support to the notion that the expression levels of ABCB1 and SLFN11 are potential biomarkers for cancer cell line sensitivity to multiple drugs (Ballestrero et al, 2017;Chen and Sikic, 2012;Pietanza et al, 2018;Vaidyanathan et al, 2016). Our results also revealed that SPRY2 expression is positively correlated with the sensitivity of the cancer cell lines to many MEK inhibitors from GDSC, suggesting that SPRY2 expression may be a predictive biomarker for the effectiveness of MEK kinase inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…Among those drugs for which gene expression data can reasonably predict a cancer cell line's sensitivity, we identified many known drug-gene interactions as well as several novel associations. Our results are consistent with and lend additional support to the notion that the expression levels of ABCB1 and SLFN11 are potential biomarkers for cancer cell line sensitivity to multiple drugs (Ballestrero et al, 2017;Chen and Sikic, 2012;Pietanza et al, 2018;Vaidyanathan et al, 2016). Our results also revealed that SPRY2 expression is positively correlated with the sensitivity of the cancer cell lines to many MEK inhibitors from GDSC, suggesting that SPRY2 expression may be a predictive biomarker for the effectiveness of MEK kinase inhibitors.…”
Section: Discussionsupporting
confidence: 87%
“…are potential biomarkers for cancer cell line sensitivity to multiple drugs [30,[59][60][61]. Our results also revealed that SPRY2 expression is positively correlated with the sensitivity of the cancer cell lines to many MEK inhibitors from GDSC, suggesting that SPRY2 expression may be a predictive biomarker for the effectiveness of MEK kinase inhibitors.…”
Section: Discussionsupporting
confidence: 58%
“…to multiple categories of DNA-damaging antitumor agents including topoisomerase I and II inhibitors, PARP inhibitors, and platinum compounds in a variety of cancers[54][55][56][57][58][59][60][61][62].Figure S3shows the midpoint rooted hierarchical clustering [44] of 1302 natural products based on their log(GI50) values across the NCI-60 cell lines. Those compounds for which the sensitivity was significantly correlated with SLFN11 expression (FDR adjusted P < 0.05) are highlighted in yellow.…”
mentioning
confidence: 99%